2012
DOI: 10.1182/blood-2011-08-370536
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 regulates HGAL expression and increases lymphoma cell motility

Abstract: IntroductionHGAL (Human Germinal-center Associated Lymphoma) is a germinal center (GC) specific gene involved in negative regulation of lymphocyte and lymphoma cell motility by at least 2 distinct molecular mechanisms. HGAL directly and independently binds to both actin and myosin II proteins, increasing binding between F-actin and myosin II and inhibiting the ability of myosin to translocate actin by reducing the maximal velocity of myosin head/actin movement. 1,2 In addition, HGAL inhibits lymphocyte motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 49 publications
0
45
0
1
Order By: Relevance
“…Some studies demonstrated that miR-155 could act as an oncogene to contribute to multiple facets of tumorigenesis, such as proliferation, motility, invasion, differentiation, angiogenesis, etc. [6][7][8][9]. Consistently, silencing of miR-155 could inhibit apoptosis, proliferation and migration in cancer cells [10].…”
Section: Introductionmentioning
confidence: 71%
“…Some studies demonstrated that miR-155 could act as an oncogene to contribute to multiple facets of tumorigenesis, such as proliferation, motility, invasion, differentiation, angiogenesis, etc. [6][7][8][9]. Consistently, silencing of miR-155 could inhibit apoptosis, proliferation and migration in cancer cells [10].…”
Section: Introductionmentioning
confidence: 71%
“…[18][19][20][21][22][23] To date, a few direct targets of miR-155, such as suppressor of cytokine signaling 1, SH2-containing inositol 5'-phosphatase, Sma-and Mad-related protein 2, hexokinase 2, casein kinase-1α, and human germinal center-associated lymphoma, have been identified by luciferase report assay. 15,16,21,[24][25][26][27][28] In endothelial cells, type 1 angiotensin II receptor, BACH1, and cysteine-rich protein 61 have been validated to be regulated by miR-155. [29][30][31] Notably, previous work showed that the level of circulating miR-155 is remarkably reduced in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Она влияет на развитие практически всех лимфом, за исключением мантийно-клеточной, и хо-тя молекулярные механизмы возникновения разных форм пока не совсем расшифрованы, они, очевидно, связаны с функционированием сигнальных путей, отвечающих за нормальный лимфогенез [39,40], в частности, вышеупомянутый сигнальный путь JAK / STAT / SOCS [23,26]. Нельзя не отметить, что ингибирование экспрес-сии miR-155 в клетках лимфомы линии SNK-6 приво-дит к снижению пролиферации и усилению апоптоза, которое связывают с регуляцией экспрессии гена FOXO3a [23].…”
Section: гемобластозы и Mir-155unclassified